Тернопільщина в роки Другої світової війни - Бармак, Микола; Barmak, M. (Волинський національний університет імені Лесі Українки, 2012)
Розглянуто питання перебування Тернопільщини в умовах Другої світової війни, впровадження спочатку радянських, а згодом німецьких органів влади, описано функціонування фашистського окупаційного режиму в краї; визволення від окупантів. It is considered the problem of Terno-pil’shchyna being under circumstances of World War II, the introduction at first Soviet, and then German local authorities, the functioning of fascist occupation regime in the region and the process of release from the occupants are described.
Ternopil Region During the Second World War
Keywords: Тернопілля; окупаційний режим; репресії; визволення; Ternopillia; occupation regime; repressions; release